Pengaruh Good Corporate Governance Terhadap Tax Avoidance (Penghindaran Pajak) - Rachyu Purbowati (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2021)
This study aims to determine how much influence Good Corporate Governance has on Tax Avoidance. Good Corporate Governance is checked with the Independent Board of Commissioners, Institutional Ownership, Managerial Ownership and the Audit Committee on Tax Avoidance. This research is a quantitative study using secondary data obtained from annual financial reports on the IDX website. The population of this research is 27 companies from 2016-2019. The sampling technique used in this research was purposive sampling technique. The samples obtained were 9 companies. The results of this study indicate that (1) the results of testing the regression model hypothesis simultaneously show that the Independent Commissioner, Institutional Ownership, Managerial Ownership, and the Audit Committee have no effect on Tax Avoidance.